Effect of nonmodified and organically modified montmorillonite incorporation on polyamide 6/acrylonitrile‐ethylene‐propylene‐diene‐styrene/methyl methacrylate‐co‐maleic anhydride system. Issue 6 (13th October 2021) - de Oliveira, Amanda Dantas; de Castro, Lucas Daniel Chiba; Gonçalves Beatrice, Cesar Augusto; de Almeida Lucas, Alessandra; Pessan, Luiz Antonio
Abstract: Nanocomposites based on polyamide 6/acrylonitrile‐ethylene‐propylene‐diene‐styrene/methyl methacrylate‐co‐maleic anhydride (PA6/AES/MMA‐MA) system were prepared through the incorporation of the nonmodified montmorillonite Cloisite® Na + (Nano Na + ) and the organically modified montmorillonite Cloisite® 30B (Nano 30B) via melt blending process. Nano Na + exhibits an intercalated structure with large tactoids and mechanical performance comparable to the ternary blend. On the other hand, Nano 30B exhibits exfoliated structure and a significant enhancement of stiffness as a result of the high interaction between PA6/Cloisite® 30B. After an extensive investigation concerning the crystalline structure of the nanocomposites, we hypothesized that such high interaction between PA6/Cloisite® 30B hampers the crystallization process of PA6, so small and imperfect γ ‐crystals were predominantly formed in Nano 30B. In turn, the low interaction between PA6/Cloisite® Na + did not negatively affect the PA6 crystallization process; quite the opposite, we believe that the large tactoids observed in Nano Na + might be acting as nucleation sites, resulting in a large degree of crystallinity and a considerable ratio of α ‐phase. Abstract : Concerning polymer/montmorillonite (MMT) nanocomposites, the presence or absence of organic modifier on the surface of silicate layers determines the type and intensity of the interaction between the matrix and nanofiller. In turn, such interaction is one of the key parameters governing the nanostructure, as well several properties of the obtained material. In this way, a model comprising the presence/absence of organic modifier, nanostructure, and final properties is proposed for a typical polyamide‐based nanocomposite.